Factors Associated with Nutritional Status of Pregnant Women at Majalaya Public Health Center in 2024 - Khairunnisa, Ika; Puspa Wati Manik, Tri Arini; Mulyani, Neng; Mulyani, Yunita (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: The nutritional and health status of pregnant women in Indonesia remains a public health concern. Malnutrition during pregnancy is influenced by several factors, including education level, maternal age, and parity. Education affects health behavior, while pregnant women under 20 and over 35 years are at higher risk of experiencing Chronic Energy Deficiency (CED). High parity can also contribute to maternal and fetal health complications. Objective: This study aims to determine the association between maternal education, age, and parity with the nutritional status of pregnant women at the Majalaya Health Center in 2024. Method: A quantitative study was conducted using an analytical survey with a cross-sectional design. The independent variables were maternal education, age, and parity, while the dependent variable was nutritional status. A total sampling technique was used, involving 61 pregnant women. Data were analyzed using the Chi-square test with the Statistical Product and Service Solution (SPSS) software. Results and Discussion: The findings showed that 30.3% of women with low education levels experienced CED, compared to 10.7% with higher education. Among those at risk age (<20 or >35), 30.0% experienced CED, while only 17.1% at non-risk age did. Women with high parity showed a 33.3% incidence of CED, while those with low parity had 13.5%. There was a significant association between maternal education, age, and parity with nutritional status. Conclusion: Education, age, and parity are significantly associated with the nutritional status of pregnant women. It is recommended that health promotion programs be enhanced to improve maternal knowledge and practices during pregnancy, particularly for those with low education, high parity, and at-risk age groups.